1424. Examining the Relationship Between Vancomycin Area Under the Concentration–Time Curve and Serum Trough Levels in Adults with Presumed or Documented Staphylococcal Infections. (26th November 2018) - Clark, Laura; Skrupky, Lee P; Servais, Ryan; Brummitt, Charles F; Dilworth, Thomas J
Abstract: Background: Recent studies evaluating area under the concentration–time curve (AUC)-guided vancomycin dosing have reported reduced drug exposure and nephrotoxicity as compared with traditional trough-guided (target 15–20 mg/L) dosing for invasive infections, but studies exploring the relationship between vancomycin trough concentration and AUC remain limited. Methods: This was a retrospective observational study performed at two hospitals within a large health system. Patients receiving AUC-guided vancomycin dosing for a presumed or confirmed invasive staphylococcal infection between December 1, 2016 and July 31, 2017 were evaluated. Two steady-state serum vancomycin levels were obtained in each patient and used to determine the 24-hour AUC/MIC ratio; the AUC/MIC target was >600 mg/L hour for endocarditis and >400 mg/L hour for all other sources. The relationship between trough and AUC was explored using the Pearson product-moment correlation coefficient. Patient demographics and dosing details were also collected. Results: Thirty-four patients were included in the study, with two patients having vancomycin levels drawn twice (36 sets of levels). Most patients were located in an ICU (91.2%) and 85.3% of patients had bacteremia, pneumonia or endocarditis. An organism was recovered from 28 patients (82.3%) of which 21 (75%) had a vancomycin MIC of 1 mg/L and 25 were S. aureus (89.3%). The mean vancomycin trough was 16.6 ± 6.1 mg/L and the mean AUC/MIC was 588 ± 156 mg/L hour. There was a strong correlation between vancomycin trough and 24-hour AUC ( R 2 = 0.731; P < 0.001; Figure 1). The rate of 24-hour vancomycin AUC/MIC target attainment was 91.2% ( n = 31/34). Among patients with a trough >9 mg/L, 100% ( n = 33) achieved AUC/MIC values >400 mg/L hour and 94% were >500 mg/L hour. Conclusion: Targeting a vancomycin trough between 15 and 20 mg/L frequently results in an AUC/MIC in excess of the target identified for efficacy. Considering the strong correlation observed between trough and AUC alongside practical challenges associated with wide-scale implementation of AUC monitoring, a reduced target trough in conjunction with targeted application of AUC-guided dosing warrants further evaluation. Disclosures: All authors: No reported disclosures.